2018
DOI: 10.1007/s00464-018-6217-x
|View full text |Cite
|
Sign up to set email alerts
|

Technique, safety, and feasibility of EUS-guided radiofrequency ablation in unresectable pancreatic cancer

Abstract: EUS-guided RFA is a feasible and safe minimally invasive procedure for patients with unresectable PDAC. Further studies are warranted to demonstrate the impact of EUS-guided RFA on disease progression and overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 20 publications
2
83
0
Order By: Relevance
“…The remaining one study had technical success of 94 %. Scopelliti et al, who had a 100 % technical success rate, pointed out logistical and anatomical limitations such as scarring from previous radiation or inability to maneuver the stiff probe to the target site [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining one study had technical success of 94 %. Scopelliti et al, who had a 100 % technical success rate, pointed out logistical and anatomical limitations such as scarring from previous radiation or inability to maneuver the stiff probe to the target site [3].…”
Section: Discussionmentioning
confidence: 99%
“…An internal cooling system is sequentially employed to prevent thermogenic damage to surrounding tissue. Postoperative computed tomography (CT) scans were performed to compare the change in size of the enhanced tissue of the tumor to a preoperative CT, as well as to assess for any complications [3].…”
Section: Eus-rfa Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…RFA treatment exerts therapeutic effect mainly through local thermal ablation to tumor . It has been revealed that perfusion of tumor is an important factor influencing the energy distribution of thermal ablation .…”
Section: Introductionmentioning
confidence: 99%